338 Effect of Calcium Oxide Treatment of Barley Straw on In Vitro & In Situ Digestibility. (7th December 2018) - Stehr, K; Santos, L; Ribeiro, G; McKinnon, J; Gibb, D; McAllister, T
Abstract: Improving the nutritional value of low quality forages is one strategy to lower beef cattle feed costs. These experiments examined the extent to which calcium oxide (CaO) can improve the digestibility of barley straw, compared to barley and corn silage. Barley straw was hydrated to 50% moisture and CaO was added at 5% of DM. Dry matter and NDF digestibility were measured in vitro and in situ. Cannulated heifers (4) were fed a wheat-based diet with either barley silage or barley straw. The in vitro study utilized inoculum, combined by diet, to incubate forage samples for 30h. In situ degradation of forages was measured by incubating bags in the rumen for 9 time points up to 240h, followed by kinetic analysis. CaO treatment reduced the NDF content of barley straw by 15.1%. CaO did not improve ( P=0.99 ) the in vitro NDFD of straw. CaO improved ( P<0.01) in vitro true DMD of barley straw from 48.4% to 55.8% but was still lower than that of barley or corn silage. CaO improved the in situ digestibility of barley straw. CaO increased (P=0.03 ) the DM potentially degradable fraction of straw, but it was still lower than barley and corn silage. Effective rumen degradability (ERD) of CaO straw was also improved (P<0.01), but remained lower than silages. Feeding a grain diet with straw as opposed to silage improved (p<0.01 ) kd of forages. A similar response occurred in vitro, where inoculum from heifers fed the grain-straw diet tended to have higher NDFD (P=0.07 ) and TDMD (P=0.06). CaO improved the in vitro and in situ DMD of barley straw, but no effect was observed on in vitro NDFD, likely because of the reduced NDF content of the original substrate. CaO treatment improved ERD but it did not exceed the value of barley or corn silage.